2019
DOI: 10.1039/c9ra05649a
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-small bimetallic iron–palladium (FePd) nanoparticle loaded macrophages for targeted tumor photothermal therapy in NIR-II biowindows and magnetic resonance imaging

Abstract: Nanoparticles working in the NIR-II biowindows possess larger maximum permissible exposure (MPE) and desirable penetration depth to the laser. However, most NIR-II responsive nanomaterials lack tumor targeting and Magnetic Resonance Imaging (MRI) ability. This greatly limits their applications. This study reported ultra-small bimetallic iron-palladium (FePd) nanoparticle loaded macrophages for targeted tumor photothermal therapy in NIR-II biowindows and magnetic resonance imaging. The crystal phase, morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…However, NPs in the range of tens to hundreds of nanometers have mostly been applied for the development of macrophage-mediated drug delivery and cancer therapy, whilst NPs smaller than ten nanometers have long been ignored. [39] To the best of our knowledge, there are only two published literature addressing the feasibility of using macrophages for the delivery of ultrasmall NPs to tumors, [21,22] and no study has been conducted to compare the efficiency of macrophage-mediated active targeting with the EPR-mediated passive targeting for ultrasmall NPs. Thus, we next examined the performance of as-prepared Au NP-macrophage systems for tumor targeting using the subcutaneous tumor mouse model.…”
Section: Passive Versus Active Tumor-targeting Delivery Of Sub-5 Nm A...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, NPs in the range of tens to hundreds of nanometers have mostly been applied for the development of macrophage-mediated drug delivery and cancer therapy, whilst NPs smaller than ten nanometers have long been ignored. [39] To the best of our knowledge, there are only two published literature addressing the feasibility of using macrophages for the delivery of ultrasmall NPs to tumors, [21,22] and no study has been conducted to compare the efficiency of macrophage-mediated active targeting with the EPR-mediated passive targeting for ultrasmall NPs. Thus, we next examined the performance of as-prepared Au NP-macrophage systems for tumor targeting using the subcutaneous tumor mouse model.…”
Section: Passive Versus Active Tumor-targeting Delivery Of Sub-5 Nm A...mentioning
confidence: 99%
“…But the majority of methods reported in the literature to date used Au NPs with a size of tens to hundreds of nanometers for the cell-mediated tumor-targeting delivery, only a few studies have examined the feasibility of using immune cells or stem cells to deliver ultrasmall NPs. [21][22][23][24][25] The biggest challenge to deliver ultrasmall NPs to tumors is to guarantee the stability of NP-cell systems, because smaller NPs generally have a fast rate of exocytosis, leading to a rapid disassembly of NP-cell systems and redistribution of NPs in vivo. [26] Therefore, whether this kind of active tumor-targeting strategy works for the sub-5 nm Au NPs still needs to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…3C , Yang et al reported ultra-small bimetallic FePd-loaded macrophages for targeted tumor photothermal therapy in NIR-II bio-windows and magnetic resonance imaging. 55 In addition, the constructed porous Au@Pt structure was further explored for the properties of porous Au@Pt NPSs in relieving the oxidative stress damages as well as in tumor growth inhibition by chemo–photothermal co-therapy. The porous structure offered the possibility while using this structural space for medicine loading such as doxorubicin (DOX).…”
Section: Metal-based Heterogeneous Structures As Functional Candidate...mentioning
confidence: 99%
“…A tumor volume reduction of ~ 90%, with insignificant organ toxicity, was observed with the use of this nano-biohybrid as compared to the control group. The observed results present an excellent platform that can be explored further clinically for combining photodynamic therapy and MRI imaging [ 280 ].…”
Section: Bio-nanocarriers For Clinical Management Of Lung Cancermentioning
confidence: 99%